Transcriptome profiling of potato plant stems challenged with Pectobacterium carotovorum subsp. brasiliense and elucidation of the role of small RNAs in Pectobacterium survival mechanisms - Moleleki, Lucy N. (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2016.